Energy and environmental impact for development of multipurpose PADMA bridge - R, Sharmin; Muhammad Mahbubur, Rashid; M.M, Ferdaus; Raju, Ahamed (Universiti Malaya, 2014)
The Padma Multipurpose Bridge Design Project comprises a new fixed crossing of the Padma River, of approximately 6.15 km long. In order to complement the construction of the Project, it is mandatory to plan and to develop road, railway, transmission and telecommunication networks to connect with the south western part of the country. The main purpose of this study is to harvest energy and assesses the cumulative environmental impact that has been caused by river training, construction and development works. The impacts are classified in few categories- land acquisition and resettlement, transport and economy. Energy harvesting though solar panel and speed breaker is proposed to install for sake of economic and environmental improvement. Here, the probable environmental impacts, both positive and negative are properly analyzed which represents a clear picture of the environmental impact scenario of any multipurpose bridge construction.